Development of Enzymatic Method for Environmental Monitoring of Monocrotophos - Devi Yalavarthy2, Uma Maheswara Rao Ganguru1; Prameela (Recent Research in Science and Technology, 2011)
In the present study, we have developed a simple, low cost, viable and sensitive enzymatic method for detection, separation and identification of an organophosphorus pesticide, monocrotophos from environmental samples. This technique is based on the inhibition of enzyme, Succinate Dehydrogenase (SDH) (EC.No. 1.3.5.1). The enzyme (SDH) specifically binds to the substrate (sodium succine) and develops colour in the presence of chromogenic reagent. This chromogenic reagent contains INT (2-(4- Ido-phenyl)-3-(4-nitrophenyl)-5 phenyl tetrazolium chloride) and PMS (N-methyl phenazonium methosulphate). Chicken liver, egg albumin and Escherichia coli were used as the sources of SDH enzyme. Simple adsorption technique has applied for the preparation of enzyme and substrate strips using wattman no. 3 filter paper as a solid support system. Aqueous standards of monocrotophos was prepared and tested for the inhibition. The concentration as low as six micrograms of monocrotophos was successfully detected. Separation and identification of monocrotophos was done by micro thin layer chromatography (TLC) combined with the enzymatic method using the same enzyme inhibition principle. The developed enzymatic method was successfully applied for detection, separation and identification of monocrotophos from environmental samples.